Sensor datasets report from the value-proposition Ag-plot testing of automated field data collection and monitoring tools in Guatemala - 2023 - Estrada Vargas, Oscar H.; Jimenez, Daniel Ricardo; Ramos, Gresia Dalal; Martínez, Jesús David; Van Loon, Jelle Filip (2023)
As part of the Digital Innovation initiative, the Alliance Bioversity International -CIAT and CIMMYT, established a digital plot at the San Carlos University, CUNORI, in Chiquimula, Guatemala. A set of meteorological, soil and crop data have been collected since July 2023. The information comes in that first stage from two strategically located weather stations and a soil device that measures soil moisture, salinity, and temperature. This data will be essential to understand environmental conditions and the behavior of climate, soil, and plants in the region, and enable informed crop management decisions for data-driven agronomy.